The Effect Of Using Cooperative Learning On Learning and Retaining Some Basic Skills of Floor Exercises In Women Artistic Gymnastics - Laiz, Kholoud (Journal of Physical Education, 2007)
Leaning style has an important role in learning different skills in gymnastics. This sports needs from the teacher to use more than one style including cooperative style. The problem of the research was the variation in the students’ performance during gymnastic lesson and this might be due to the teaching style used. The aim of the research was to identify the differences between the effect of using cooperative teaching style in learning and retaining some basic skills in floor exercises in gymnastics. The researcher hypothesized that there are statistical differences in learning and retaining some basic skills in floor exercises in gymnastics. The subjects were (50) fifth grade female students of preparatory school. The tools and instruments used in the research were described in details as well as the motor skills and the field study. After analyzing the data the researcher came up with many conclusions. One of the most important conclusions was cooperative teaching contributed in increasing the level of learning and retaining the basic skills in gymnastics. Finally she recommended using cooperative teaching for its positive effect in learning artistic gymnastics.